New Cleavable Spacers for Tandem Synthesis of Multiple Oligonucleotides - Yamamoto, Kazuki; Fuchi, Yasufumi; Okabe, Masaya; Osawa, Takashi; Ito, Yuta; Hari, Yoshiyuki (Synthesis, 2021)
In solid-phase oligonucleotide synthesis, a single oligonucleotide is generally acquired from a column loaded with a specific solid support. Herein, we have developed new cleavable spacer (CS) derivatives for tandem synthesis of multiple oligonucleotides on a single column. Four CS analogues were designed, synthesized, and inserted between two oligonucleotide sequences using an automated oligonucleotide synthesizer. The CS derivatives bearing a cyclic cis-1,2-diol exhibited efficient release of the two oligonucleotides under commonly employed basic conditions of aqueous ammonia. Among the CS analogues, it was found that CS with a robust structure can potentially be applied as a spacer molecule in the tandem synthesis of multiple oligonucleotides in a single sequence.
Keywords: oligonucleotide synthesis; tandem synthesis; cleavable spacers; phosphoramidites; 1,2-diol derivatives